Nucleolar areas and the nucleolar/nuclear ratios in megacolonic neurons of chagasic patients - Abdo-Banhos, C. R.; Bicudo, H. E.M.C. [UNESP]; Manzatto, A. J. [UNESP] (My University, 1998)
Data were recorded on the mean nucleolar areas of neurons from the megacolon of chagasic patients, and neurons from the colon of non-chagasic subjects. The significant differences obtained were indicative of a higher level of nucleolar activity in the megacolon neurons of the chagasic, than in the colon of non-chagasic, patients. Chagasic and non-chagasic individuals in the samples analysed were not significantly different in their nucleolar/nuclear ratios, due to an increase of nuclear areas in parallel with an increase of nucleolar areas in chagasic subjects.
Keywords: Chagas's disease; Megacolonic neurons; Nucleolar activity